Saussurea odorata (Asteraceae), a new species from western Mongolia - Pyak, Elizaveta A.; Pyak, Andrei I.; Madyka, Violetta V. (Phytotaxa, 2020)
A new species of Asteraceae, Saussurea odorata, is described here based on morphological evidence. The new species was discovered in the southern part of the Mongolian Altai Mountains, Möst Sum (District), Khovd Aimag (Province), Mongolia. Morphological comparisons showed that S. odorata is similar to S. saichanensis and S. krylovii, but can be distinguished by its much-branched caudex, a larger number of capitula in a dense racemose synflorescence, and a strong odor due to the high density of glandular trichomes on both surfaces of leaves. Detailed illustrations, pictures of living plants, as well as a key for identification are presented.